Integrative Holistic Development Program in School Integral Hidayatullah Yaa Bunayya Batang - Yuniarto, Jefri Tri; Khasanah, Uswatun (Universitas Negeri Semarang, 2014)
This study used a qualitative descriptive method that aims to understand the phenomenon of what is experienced by the study subjects eg behavior, perception, motivation, action, and other holistically and by means of a description in the form of words and language, in a specific context naturally and by utilizing a variety of natural methods. The subjects in this study were principals, teachers and chairman of the foundation. Methods of data collection by using observation, interviews, and documentation. Analysis of the data with data reduction, data display, and conclusion drawing and verification. The results of the data analysis and discussion concluded that the preparation of development programs in the School of Integral Holistic Integrative Hidayatullah Yaa Bunayya rod to provide essential services to the child so that the child can be met, in the provision of services to children of its implementation have been able to organize the development of integrative holistic early childhood education programs well or succeed in provide services to children with a holistic and integrative. School of Integral Hidayatullah Yaa Bunayya Rod trying to prepare what is needed to provide a holistic and integrative services to children, both of the facilities and infrastructure to prepare teachers who understand the needs of all children, holistic services for children. The school seeks to provide educational children in accordance with the principles of early childhood learning and in the process integrate with the values of divinity and equip the daily habit of planting Islamic character. Habituation Islamic way of life taught by role models whereas Qur'an and Hadist al is a source of inspiration in any learning process. Through the planning, implementation and evaluation of integrative holistic early childhood education good, so that it can be said the school integral Hidayatullah is ready in developing or organizing service early childhood programs integrative holistic one-stop service.How to citeYuniarto, J., & Khasanah, U. (2014). Integrative Holistic Development Program in School Integral Hidayatullah Yaa Bunayya Batang. Indonesian Journal Of Early Childhood Education Studies, 3(1), 31-36. doi:10.15294/ijeces.v3i1.9473